2011
DOI: 10.2174/1876396001104010136
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-Stabilized Zinc Gluconate Has Similar Bioavailability than Zinc Sulfate In a Zinc Fortified Probiotic Food

Abstract: Objective: In this study, we evaluated zinc gluconate stabilized with glycine (GZ) and sulfate (SZ) in fermented milk as vehicle. Zinc bioavailability was evaluated in an animal model (Sprague Dawley rats) for both zinc sources in the vehicle with a probiotic (Lactobacillus casei DN114001).Results: For growth parameters, higher weight gain and femur weight values were observed when probiotic and zinc were provided together, independent of the source (weight gain: SZ 81.4g±4.0g; GZ 81.8g±4.0g and 70.2g±12.5g wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Animal model studies suggested that the efficacy of probiotics may be increased by the combination of probiotics and synergistically acting prebiotic components [ 82 ] like FOS [ 83 ], phytins [ 84 ], maltodextrin KMS X-70 [ 85 ] working together with zinc [ 86 ]. Likewise, rat model studies have shown that the combination of probiotics and zinc can improve zinc bioavailability [ 87 ]. This may be due to a synergistic effect between the probiotic and zinc to improve histomorphology (villus height and total goblet cell count) of the intestine [ 88 ] and its integrity [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Animal model studies suggested that the efficacy of probiotics may be increased by the combination of probiotics and synergistically acting prebiotic components [ 82 ] like FOS [ 83 ], phytins [ 84 ], maltodextrin KMS X-70 [ 85 ] working together with zinc [ 86 ]. Likewise, rat model studies have shown that the combination of probiotics and zinc can improve zinc bioavailability [ 87 ]. This may be due to a synergistic effect between the probiotic and zinc to improve histomorphology (villus height and total goblet cell count) of the intestine [ 88 ] and its integrity [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…These processes influence the physiological development of the gastrointestinal tract of the chick in the first 21 d after hatching, including the length of the intestines and gut pH ( Shehata et al, 2021 ). Previous research using rats ( Tesán et al, 2011 ) indicates that the bioavailability of zinc increases when used in combination with probiotics, and it acts synergistically with the probiotic to increase villus height and the total number of goblet cells ( Shah et al, 2019 ). Therefore, combined administration of zinc and probiotics increases the absorption of zinc, which improves production parameters by stimulating metabolism of proteins, sugars and fats ( Liu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%